Physiotherapeutic interventions in the treatment of patients with diabetic foot ulcers: a systematic literature review. (March 2023) - Medeiros, Sabrina; Rodrigues, Alexandre; Costa, Rui
Abstract: Background: Diabetic foot ulcers are chronic wounds that are difficult to heal, with a high rate of recurrent hospitalizations. Due to its multifactorial complexity, treatment must be considered as multidisciplinary, with adjuvant therapy required to aid the healing process. Objectives: To identify physiotherapeutic interventions for the treatment of diabetic foot ulcers through a systematic literature review. Data sources: PubMed, Cochrane Library, SciELO and Web of Science were searched in April 2020. Study selection or eligibility criteria: The inclusion criteria for this review were: randomised controlled trial published in the last 5 years; written in Portuguese, English or Spanish; subjects aged> 18 years with a diagnosis of diabetic foot ulcers; and physiotherapeutic intervention in combination with multidisciplinary wound management. The methodological quality was assessed using the PEDro scale. Results: Eight studies were included. Physiotherapists can treat diabetic foot ulcers using therapeutic exercises, electrotherapy, manual therapy and assistive technologies. All physiotherapeutic interventions were adjuvant to standard treatment for wounds provided by other health professionals. The main outcomes were wound size and healing time, with highly favourable results obtained for the experimental groups compared with the control groups. Conclusions: Therapeutic exercise, electrotherapy, manual therapy and assistive technologies are physiotherapeutic modalities that, when combined with standard treatment, have been shown to be beneficial in the healing of diabetic foot ulcers.